2014
DOI: 10.1097/bot.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Semiextended Intramedullary Nailing of the Tibia Using a Suprapatellar Approach

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 20 publications
1
51
0
1
Order By: Relevance
“…However, the authors reported that there was trend toward greater symptomatic knee pain in the infrapatellar group. Furthermore, Sanders et al [ 15 ] reported on 56 consecutive patients undergoing suprapatellar nailing in the semiextended position. These authors did not identify any patients with postoperative anterior knee pain at 12 months follow-up except one patient who presented with peri-incisional pain around the knee [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the authors reported that there was trend toward greater symptomatic knee pain in the infrapatellar group. Furthermore, Sanders et al [ 15 ] reported on 56 consecutive patients undergoing suprapatellar nailing in the semiextended position. These authors did not identify any patients with postoperative anterior knee pain at 12 months follow-up except one patient who presented with peri-incisional pain around the knee [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nailing in the semiextended position has recently gained significant attention in the orthopaedic literature [ 12 15 ]. Nailing in the semiextended position using a medial parapatellar approach has been suggested by Tornetta and Collins as a method to avoid apex anterior deformities [ 16 ].…”
Section: Surgical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is possible that fibula fracture may not occur with tibia fracture in lowenergy injury. [1,2] Fixation of the accompanying fibula fracture for stability is still a matter of debate in the surgical treatment of tibia fracture. While some authors advocate fixing fibula fracture during surgical treatment of tibia fracture, others suggest that this fixation does not have beneficial effect on stability.…”
Section: Introductionmentioning
confidence: 99%